2016
DOI: 10.5455/msm.2016.28.258-262
|View full text |Cite
|
Sign up to set email alerts
|

Adherence and Quality of Life in Patients With Type II Diabetes Mellitus in Northern Greece

Abstract: Introduction:Adherence as a concept includes various types of health-related behavior. Better medical adherence leads to improved disease control and fewer diabetes–related complications. Quality of life and medication adherence are interrelated. Patients with diabetes who adhere to their treatment can experience an improvement in quality of life and vice versa.Aim:To assess treatment adherence in patients with type II diabetes, as well as the connection between adherence and quality of life.Methodology:A desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 18 publications
4
26
1
2
Order By: Relevance
“…Overall the results of the study showed that patients with type 2 diabetes exhibited low levels of diet compliance and high levels of lower extremity care and medication adherence. This result does not coincide with the findings of previous research in Greece, which showed higher rates of diet compliance [13].…”
Section: Fig 1 Median Time Since Diagnosis Of Diabetescontrasting
confidence: 99%
See 2 more Smart Citations
“…Overall the results of the study showed that patients with type 2 diabetes exhibited low levels of diet compliance and high levels of lower extremity care and medication adherence. This result does not coincide with the findings of previous research in Greece, which showed higher rates of diet compliance [13].…”
Section: Fig 1 Median Time Since Diagnosis Of Diabetescontrasting
confidence: 99%
“…In the present study, only positive associations were observed between personal attitudes towards lower extremity care and compliance with lower extremity care with the quality of life associated with physical health. Although this result is consistent with the findings of Zioga et al [13], this study also found other correlations between all dimensions of diabetes compliance (diet, exercise, blood sugar measurement, self-care recommendations) and all dimensions of quality of life, as assessed by the SF-36 scale, which were not identified in the present study due to possible differences in the samples between the two studies, but also possibly due to differences in the data collection tool for adherence to the antidiabetic treatment. Possible, some other factors may contribute to the quality of life of sample diabetes patients, such as co mplications of diabetes, type of medication, or duration of diabetes, but these associations were not examined in the present study.…”
Section: Fig 1 Median Time Since Diagnosis Of Diabetessupporting
confidence: 94%
See 1 more Smart Citation
“…Особую актуальность и значимость проблемы HRQoL и приверженности к терапии имеют при хро-нических заболеваниях, требующих длительного, не-редко пожизненного, лечения. В целом ряде иссле-дований была выявлена взаимосвязь между крите-риями КЖ и показателями приверженности к лечению [3][4][5]. Так, в публикации Allhadad I.A.…”
Section: Treatment Adherence and Quality Of Life Of Patients With Staunclassified
“…и Urbayatun S. также была выявлена положительная корреляция между показателями КЖ и приверженности к медикаментозной терапии у больных сахарным диа-бетом 2 типа [4]. Взаимосвязь между приверженностью больных к лечению и их HRQoL была подтверждена и в исследовании греческих авторов [5]. В других ис-следованиях связи между КЖ и приверженностью к лечению либо не было выявлено [6], либо она была очень слабой, незначительной [7].…”
Section: Treatment Adherence and Quality Of Life Of Patients With Staunclassified